DESIGN OF THE NEW RUNWAY AT SUPADIO INTERNATIONAL AIRPORT'S RIGID PAVEMENT THICKNESS USING FAA METHOD - Deni, Natalis; Akhmadali, Akhmadali; Kadarini, S. Nurlaily (Jurnal Teknik Sipil, 2023)
Supadio International Airport in Pontianak is a gateway for many domestic and international tourists. In order to boost West Kalimantan's economy and tourism, PT. Angkasa Pura II (Persero) wants to expand the Supadio International Airport by adding a second runway. This article looks at how the FAA (Federal Aviation Administration) method was used to plan the thickness of the rigid pavement on the new runway at Supadio International Airport. The expected number of people and aircraft will be calculated using the double-moving average method. The anticipated time frame is 2035, with 12.763.479 passengers and 121.782 aircraft movements annually. The Airbus A330-300 requires the most considerable thickness of the concrete slab, consisting of dual tandem wheel types and a maximum take-off weight (MTOW) of 533.519 lbs. As the original soil is in poor condition, a 52.5-cm-thick embankment is required to achieve a CBR value of 6%. The rigid pavement thickness design result for the design life of 2035 is as follows: surface course = 56,39 cm, subbase course = 15,24 cm, stabilized subgrade/base soil = 52,5 cm for critical areas, and a surface course of 50,751 cm, subbase course = 13,716 cm, and stabilized subgrade/base soil = 52,5 cm for non-critical soil.